Genotype F of Hepatitis B: Response to Interferon. Issue 4 (May 2015) - Venegas, Mauricio; Poniachik, Jaime; Fuster, Francisco; Hurtado, Carmen; Villanueva, Rodrigo A; Brahm, Javier
Background: The relevance of HBV genotype diversity on interferon (IFN) therapy outcome in chronic hepatitis B patients has recently been highlighted. Data available for genotype F is poor. The aim of this work was to analyse the response of HBV genotype F to treatment with IFN. Additionally, response was analysed according to the role of single nucleotide polymorphisms (SNPs) near to the IL28B gene. Methods: A total of 29 HBeAg-positive patients with chronic infection were included with a median age 47 (18–68) years. Of them, 27 were male. One patient was treated with standard IFN-α for 16 weeks, 6 patients received PEG-IFN-α2a 180 mg weekly for 24 weeks and 22 patients for 48 weeks. Response to treatment was defined as loss of HBeAg, anti-HBe seroconversion and decline of HBV DNA level to below 3 log of baseline (IU/ml) at the 6-month of follow-up. The SNPs rs12979860, rs12980275 and rs8099917 were studied by PCR-RFLP. Results: The overall response was obtained in 18 (62%) patients, including one patient who was treated with standard IFN. Additionally, a total of 9 (31%) patients cleared HBsAg, with appearance of anti-HBs. The viral load was undetectable in all of these patients. The same IL28B variants associated with IFN response in HCV infections were also more frequently found in HBV patients compared with non-responders. Conclusions: Our study indicates that treatment with IFN is effective in patients with HBV genotype F.